2020
DOI: 10.4038/slja.v28i2.8547
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of serratus anterior muscle block as a part of multimodal analgesic regimen in patients undergoing modified radical mastectomy

Abstract: Background: The quest for optimal analgesia after modified radical mastectomy has made anaesthesiologist steer its way into the arena of ultrasound guided interfascial blocks. Providing round the clock post-operative analgesia is standard care of treatment provided in our institution to enhance early recovery and prevent morbidity secondary to chronic pain syndromes. We hypothesised that administering serratus anterior muscle (SAM) block as a part of multimodal analgesia would be more efficacious in providing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…The years of publication of these studies ranged from 2017 to 2021, and the sample size ranged from 40 to 116. Overall, 7 trials, 5 trials, and 1 trial used bupivacaine [ 26 , 27 , 30 , 32 , 34 , 36 ], ropivacaine [ 12 , 29 , 33 , 35 , 37 ], and levobupivacaine [ 28 ] as a local anaesthetic, respectively. The volume of the local anaesthetic was 20–40 mL, and its concentration was 0.25%–0.5%.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The years of publication of these studies ranged from 2017 to 2021, and the sample size ranged from 40 to 116. Overall, 7 trials, 5 trials, and 1 trial used bupivacaine [ 26 , 27 , 30 , 32 , 34 , 36 ], ropivacaine [ 12 , 29 , 33 , 35 , 37 ], and levobupivacaine [ 28 ] as a local anaesthetic, respectively. The volume of the local anaesthetic was 20–40 mL, and its concentration was 0.25%–0.5%.…”
Section: Resultsmentioning
confidence: 99%
“…A total of 10 trials used the random sequence generation method [ 12 , 27 37 ], 9 trials explained the allocation concealment [ 12 , 26 , 28 , 30 , 33 , 35 , 36 ], 3 trials explicitly described the method of double blinding [ 12 , 28 , 36 ], and 9 trials described blinded assessors and evaluated attrition bias [ 12 , 27 , 28 , 31 , 33 37 ]. There was no selective reporting.…”
Section: Resultsmentioning
confidence: 99%
“…No significant difference was shown 6 h after surgery, probably due to the limited number of included studies. Additionally, 24 studies analyzed postoperative movement or cough pain scores with the use of SAPB in patients undergoing thoracic or breast surgery [4,5,15,16,[30][31][32][33][34][35][36][37][38]. Metaanalysis showed that compared with the control group, the SAPB group showed significantly reduced movement or cough pain scores at different postoperative time points, except for 48 h postoperatively (Figures 5-7…”
Section: Postoperative Pain Scoresmentioning
confidence: 99%
“…Nineteen studies reported 24 h postoperative opioid consumption in patients undergoing thoracic or breast surgery [5,15,16,32,33,[36][37][38][45][46][47][48]. Meta-analysis showed that SAPB significantly reduced 24 h postoperative opioid consumption compared with the control group (Figure 8) (SMD, −2.77; 95% CI, −3.56 to −1.97; P < 0.01; I 2 = 97%).…”
Section: Postoperative Opioid Consumption At Hmentioning
confidence: 99%